Educational Perspectives on Traditional Healthcare: Understanding Millennial Perceptions of the Kasai-Langger Tradition in Malay Ethnic Communities - Musa, Dahniar Th. (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study delves into the perceptions of the millennial generation in Malay ethnic communities regarding the kasai-langger tradition as a form of traditional health care, with a particular emphasis on the educational aspects of this understanding. The core objective is to assess millennials' knowledge of the herbal ingredients used in this tradition and their educational background in traditional health practices. Employing qualitative research methods, including interviews and surveys, the study measures the depth of millennials' understanding regarding the composition and preparation of the kasai-langger herbal concoction. The findings highlight a significant disparity in knowledge, where a substantial number of respondents exhibit a limited understanding of the herbal ingredients and their roles. This suggests a gap in educational exposure to traditional health practices. Only a small percentage of respondents demonstrate extensive knowledge, whereas the majority show little to no awareness of the ingredients or their substitutes. This study also investigates the impact of modern health care practices on traditional methods, revealing a trend among the younger generation towards modern health care solutions, potentially due to gaps in traditional health education. The research emphasizes the critical need for enhanced educational initiatives and information dissemination about traditional herbal practices and their ingredients. This educational focus is essential not only for the preservation of cultural heritage but also for ensuring the safe and effective use of traditional health care methods. The paper concludes with recommendations for future research and the implementation of comprehensive educational programs designed to cultivate a deeper understanding and appreciation of the kasai-langger tradition among Malay millennials, thereby bridging the knowledge gap identified in this study.